Optimalisasi Pembelajaran Pendidikan Agama Islam untuk Mewujudkan Tujuan Pendidikan Nasional di Universitas Jember: Optimization of Islamic Religious Education Learning to Realize National Education Goals at the University of Jember - Mukni’ah Mukni’ah (Fenomena, 2012)
Islamic Religious Education is an education aimed at forming a complete Muslim personality, developing human potential both physically and spiritually, and strengthening harmonious relationships between humans, Allah, and the universe. This aligns with the national education goals formulated in Law No. 20 of 2003 on the National Education System, which aims to develop students' potential to become individuals who are faithful and pious to God Almighty, noble, healthy, knowledgeable, skilled, creative, independent, and responsible democratic citizens. However, these noble goals have not been fully implemented optimally in educational units. Therefore, the University of Jember, as one of the public universities that includes Islamic Religious Education as a compulsory general course for Muslim students, must be able to optimize Islamic Religious Education learning to realize these objectives. This research aims to analyze the efforts made by Islamic Religious Education lecturers at the University of Jember to foster students who are faithful, pious, noble, and responsible. The study uses a qualitative approach with data collection methods including interviews, observations, and documentation. The results indicate that optimizing Islamic Religious Education learning requires comprehensive innovation and approaches, including additional lecture hours and supporting extracurricular activities. Pendidikan Agama Islam adalah pendidikan yang bertujuan untuk membentuk pribadi muslim seutuhnya, mengembangkan seluruh potensi manusia baik jasmaniah maupun rohaniah, serta memperkuat hubungan harmonis antara manusia dengan Allah, sesama manusia, dan alam semesta. Hal ini sejalan dengan tujuan pendidikan nasional yang dirumuskan dalam Undang-Undang Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional, yaitu mengembangkan potensi peserta didik agar menjadi manusia yang beriman dan bertakwa kepada Tuhan Yang Maha Esa, berakhlak mulia, sehat, berilmu, cakap, kreatif, mandiri, dan menjadi warga negara yang demokratis serta bertanggung jawab. Namun, tujuan mulia ini belum sepenuhnya diimplementasikan secara optimal di satuan pendidikan. Oleh karena itu, Universitas Jember sebagai salah satu perguruan tinggi negeri yang menempatkan mata kuliah Pendidikan Agama Islam sebagai mata kuliah umum wajib bagi mahasiswa Muslim, harus mampu mengoptimalkan pembelajaran Pendidikan Agama Islam agar tujuan pembelajaran tersebut dapat terwujud. Penelitian ini bertujuan untuk menganalisis upaya yang dilakukan oleh dosen Pendidikan Agama Islam di Universitas Jember dalam mewujudkan mahasiswa yang beriman, bertakwa, berakhlak mulia, dan bertanggung jawab. Penelitian ini menggunakan pendekatan kualitatif dengan metode pengumpulan data melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa optimalisasi pembelajaran Pendidikan Agama Islam memerlukan inovasi dan pendekatan yang menyeluruh, termasuk penambahan jam perkuliahan dan kegiatan ekstrakurikuler yang mendukung.